The use of a large diameter glenosphere in Reverse Shoulder Arthroplasty for proximal humeral fractures in elderly patients undergoing tuberosity removal - Rendina, Michele; Mahagna, Antonio Abed; Roveda, Giacomo; Pelliccia, Giovanni; Torriani, Camilla; Grassi, Federico Alberto (Acta Biomedica Atenei Parmensis, 2023)
Background and aim: Prosthetic replacement with reverse shoulder arthroplasty (RSA) is commonly indicated for complex proximal humerus fractures (PHFs) in elderly patients. Aim of this study was to evaluate the clinical and radiological outcomes of RSA performed for comminuted PHFs, without periprosthetic reconstruction of the tuberosities. Our hypothesis was that a large diameter glenosphere could ensure satisfactory RSA mobility and stability, regardless of tuberosity removal. Methods: We selected 32 patients (4 men, 28 women) with comminuted PHFs who underwent RSA with tuberosity excision and implantation of a 44-mm glenosphere between 2009 and 2015. Active range of motion (ROM), stability, Constant-Murley Score (CMS) (1) and Subjective Shoulder Value (SSV) (2) were assessed one year and four years after surgery. Results: Clinical and radiological information were collected for 23 patients (72%). At one-year follow-up, active anterior elevation (AE) was 96±28 degrees, external rotation with adducted arm (ER1) 9±7 degrees, external rotation with abducted arm (ER2) 14±10 degrees, internal rotation (IR) to L4; CMS was 56±10 and SSV 65±22. Clinical assessment at 4-year follow up showed a decrease in active ROM (AE was 88±20 degrees, ER1 8±2 degrees, ER2 12±10 degrees, IR to L4), CMS (52±9) and SSV (62±8). No RSA dislocation occurred during the study. In 4 patients, grade I glenoid notching without any sign of component loosening was observed 4 years after surgery. Conclusions: A large diameter glenosphere does not ensure results comparable to those achieved after RSA with tuberosity reconstruction. However, the 44-mm glenosphere was effective in preventing RSA instability